INTERFACE OF LIBRAS AND PHONOAUDIOLOGY IN ORALISMO PROCESS (Fiep Bulletin - online, 2011)
This paper aims to present the study of Brazilian sign language LBS as an important tool in the process of oralism of subjects with hearing impairments, determinants in the communication process and oralism the deaf. It discusses the LBS as a facilitating factor in describing their health problems. This is an exploratory and dialectical method, and review books, magazines, periodicals and other materials that addressed the issue, aiming to gather information about the importance of using the LBS in speech therapy, or in the communication process between deaf patients and speech therapists. Discussing issues related to sign language, which is an alternative to the socialization of the deaf and speech therapists.
Keywords: Communication; LBS; Speech